Evaluation of Renal Function in Donar Following Kidney Donation (Bangladesh Journal of Urology, 2020)
Objectives: To find out any changes in renal function in donor following kidney donation.Materials and Methods: A Hospital based prospective study was conducted in the Department of Urology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from April 2011 to September 2012, Investigations included specific gravity and urinary microalbumin, ultrasonogram of kidneys, serum creatinine, estimated glomerular filtration rate. According to inclusion and exclusion criteria a total of 37 donors were enrolled in this study. Subsequent follow up were taken at the end of three months, six months and nine months. Data were evaluated by Paired t-test, Significance was defined p value0.05) was found between baseline and the subsequent follow-up.Conclusion: Renal function of the remaining kidney in living donors does not significantly change after donor nephrectomy.Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.18-22